Simulation Study on the Spatiotemporal Difference of Complex Neurodynamics between P3a and P3b. (24th December 2020) - Wei, Xin; Ni, Xiaoli; Liu, Junye; Lang, Haiyang; Zhao, Rui; Dai, Tian; Qin, Wei; Jia, Wei; Fang, Peng
Abstract : The integration of event-related potential (ERP) and functional magnetic resonance imaging (fMRI) helps to obtain and study neural networks with high temporal and spatial resolution. EEG/fMRI data proves that in the visual tristimulus oddball paradigm, two P300 potentials (P3a and P3b) induced by target stimulation and novel stimulation are detected at the frontal-middle (Fz), center (Cz), and mid-apical (Pz) electrodes. Previous studies have shown that P3a and P3b have different spatial distributions of brain activation, but it is unclear whether they have the same neural mechanism. The purpose of this study is to determine the neuropsychological mechanisms of P3a and P3b, as well as the spatiotemporal differences in neurodynamics between the two ERP subcomponents. In a group of 25 subjects, P300 ERP induced by target stimulation and novel stimulation can be detected at the Fz, Cz, and Pz electrodes. At Cz and Fz, compared with P3b related to the target stimulus, the P3a related to the novel stimulus has a higher amplitude and the waveform declines more slowly. But at Pz, P3b has a higher amplitude than P3a. P3a appeared earlier than P3b at Cz and Fz, but the opposite phenomenon was observed at the Pz electrode. The activated brain regions of P3a included the left frontal-parietal lobe region, left anterior wedge lobe region, and right insula, while the target-driven P3b was significantly associated with BOLD changes in the bilateral fusiform gyrus, the left frontal region, and the bilateral insula. The results showed that the integration of the spatial and temporal information of the two imaging modes, namely, ERP and fMRI, proves the existence of the different brain function processes of the two P300 subcomponents. Through the analysis of the composition of P300, the results further proved that the top-down and bottom-up processing processes have played a role in the occurrence of attention capture. It is just that the modulation effects of the two processing mechanisms are different in different tasks. Therefore, it should be noted that the captured neural mechanism is not a single top-down or bottom-up processing process but should be the result of the interaction between the two.